Empowering Civics Education: A Design Thinking for Deep Learning in the 21st Century - Junaidi, Junaidi; Afrina, Batrisyia; Suganda, Fadhila Aqilahawwa; Safitri, Kartika; Abdulkarim, Aim; Komalasari, Kokom (Edukasi, 2025)
The problem in Civics Education learning often lies in the gap between the material delivered in the classroom and the realities experienced by learners in their daily lives. The introduction of Indonesia's new curriculum, namely Deep Learning, presents new challenges for educators in teaching Civics Education. Therefore, the purpose of this study is to explore the concepts of Design Thinking and Deep Learning comprehensively and to offer innovative contributions to Civics Education learning through the application of the Design Thinking approach in the learning process. This research employs a qualitative method utilizing a literature study approach. Data collection was conducted an examination of books, journals, articles, and other credible sources. Data analysis was carried out in three stages: data reduction, data display, and conclusion drawing. The results of the study show that a Design Thinking-based learning strategy for Civics Education using the Double Diamond Process Model is an innovative step to encourage the realization of Deep Learning that is relevant to the challenges of 21st-century learning. This model actively engages learners in the process of critical and creative thinking through four main stages: Discover, Define, Develop, and Deliver. By promoting a deep and reflective understanding of civic issues, this approach aligns with the principles of Deep Learning, which underscore the importance of meaningful, joyful, and mindful learning. Furthermore, it effectively cultivates learners into critical, creative, and responsible citizens in the global context.